Surface enhanced Raman spectroscopy for malaria diagnosis and intradermal measurements - Yuen, Clement (2018)
The biomarkers of many diseases such as malaria can be found in intradermal measurements. We will present two surface enhanced Raman spectroscopy (SERS) based methods for the detection of malaria biomarkers in blood, which are comparable to or outperform the standard clinical method. To eliminate the need of drawing blood, we will also report a stainless-steel microneedle based probe for direct intradermal SERS measurements. Moreover, we developed a deformable agarose needle to reduce the risk of sharp injury and cross contamination due to needle reuse. Tests in skin phantoms for glucose measurements demonstrated accuracy comparable to those traditional methods requiring blood drawing.